Relevance of Women as Managerial Leaders in the context of Environmental Turbulence - D’couto, Rita Latha (International Journal of Psychosocial Rehabilitation, 2020)
A confluence of changing values, emerging workplace trends and environmental turbulence have contributed to the perception that women’s leadership styles, skills and orientations are more suited to the needs of contemporary organizations. A large number of research studies have thrown light on the special contributions that women make when they assume positions of power and influence in organizations. This research paper presents four fundamental positions or perspectives from which the issue of promoting women in management can be viewed. It also presents an overview of the changing ideas about the relevance of women’s leadership capabilities and competencies. A review of the research on women as managerial leaders has highlighted the fact that organizations can reap a competitive advantage by developing the talent and potential of women and supporting their progress into top level management positions. It is felt that the unique traits and leadership orientations of women gain special significance in the context of today’s turbulent environment where creative and collaborative strategies alone can effectively counter global challenges.